Development of a fluorogenic small substrate for dipeptidyl peptidase-4 - Ogawa, Futa; Takeda, Masanori; Miyanaga, Kanae; Tani, Keita; Yamazawa, Ryuji; Ito, Kiyoshi; Tarui, Atsushi; Sato, Kazuyuki; Omote, Masaaki (Beilstein Journal of Organic Chemistry, 2017)
A series of aniline and m-phenylenediamine derivatives with electron-withdrawing 3,3,3-trifluoropropenyl substituents were synthesized as small and chemically stable fluorescent organic compounds. Their fluorescence performances were evaluated by converting 2,4-disubstituted aniline 1 to the non-fluorescent dipeptide analogue H-Gly-Pro-1 for the use as a fluorogenic substrate for dipeptidyl peptidase-4 (DPP-4). The progress of the enzymatic hydrolysis of H-Gly-Pro-1 with DPP-4 was monitored by fluorometric determination of 1 released into the reaction medium. The results suggest that 1 could be used as fluorophore in OFF–ON-type fluorogenic probes.
Keywords: dipeptidyl peptidase-4; fluorogenic substrate; fluorometry; small fluorescent molecule